An NS5A single optimized method to determine genotype, subtype and resistance profiles of Hepatitis C strains - Andre-Garnier, Elisabeth; Besse, Bernard; Rodallec, Audrey; Ribeyrol, Olivier; Ferre, Virginie; Luco, Caroline; Le Guen, Laura; Bourgeois, Nathalie; Gournay, Jérôme; Billaud, Eric; Raffi, François; Coste-Burel, Marianne; et al. (PLOS ONE, 2017)
The objective was to develop a method of HCV genome sequencing that allowed simultaneous genotyping and NS5A inhibitor resistance profiling. In order to validate the use of a unique RT-PCR for genotypes 1–5, 142 plasma samples from patients infected with HCV were analysed. The NS4B-NS5A partial region was successfully amplified and sequenced in all samples. In parallel, partial NS3 sequences were analyzed obtained for genotyping. Phylogenetic analysis showed concordance of genotypes and subtypes with a bootstrap >95% for each type cluster. NS5A resistance mutations were analyzed using the Geno2pheno [hcv] v0.92 tool and compared to the list of known Resistant Associated Substitutions recently published. In conclusion, this tool allows determination of HCV genotypes, subtypes and identification of NS5A resistance mutations. This single method can be used to detect pre-existing resistance mutations in NS5A before treatment and to check the emergence of resistant viruses while undergoing treatment in major HCV genotypes (G1-5) in the EU and the US